Towards an Ideal Madrasah: A Model of Developing Religious Values in Madrasah - Habibur Rahman; Rizky Ardian Khoirul Putera; Adyaksa; Samsul Susilawati (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
This study aims to analyze the strategy of strengthening religious values at MTs Badrussalam Indonesia, located in Malang. This research approach is qualitative with a case study design through data collection of observation, interviews, and documentation, focusing on the madrasah's approach in shaping students' religious character through the curriculum, school culture, and extracurricular activities. Test the validity of the data with credibility, transferability, dependability, and confirmability. The Miles & Huberman interactive model is used for data analysis, which includes presentation, reduction, and verification of conclusions. This study reveals the success of MTs Badrussalam Indonesia in integrating the five dimensions of religiosity according to Glock and Stark's theory into the education system as a whole. Belief through prayer and the role of the homeroom teacher as a religious counselor. Rituals through dhuha prayer, BMQ (Qur'an Reading Guidance), and extracurricular religious activities. Religious experience through spiritual activities such as tawassul and teacher motivation based on religious values. Knowledge through the integration of science and religion, including in the princess program. Moral consequences through the 5S culture, teacher respect, and the SASIS (Sambut Salam Siswa) program. The integration model of religiosity and education based on national education standards (SNP) PP. No. 4 of 2022 is the novelty of this research. MTs Badrussalam Indonesia offers a comprehensive approach that balances students' academic achievement with the formation of their religious character. This model can serve as a prototype of religious character-based education that is relevant to be implemented in similar educational institutions.